1989
DOI: 10.1210/endo-125-2-971
|View full text |Cite
|
Sign up to set email alerts
|

In VivoHypothalamic Release of Thyrotropin-Releasing Hormone after Electrical Stimulation of the Paraventricular Area: Comparison between Push-Pull Perfusion Technique and Collection of Hypophysial Portal Blood

Abstract: Unilateral electrical stimulation for 15 min of the paraventricular area of anesthetized rats induced a 2- to 3- fold increase in plasma TSH levels and caused an increased release of TRH into hypophysial stalk blood from 217 +/- 25 to 530 +/- 90 pg/15 min (n = 6). This experimental model was then used to determine the in vivo hypothalamic release of TRH by push-pull perfusion of either the mediobasal hypothalamus (MBH) or anterior pituitary (AP). Before stimulation, TRH release per 15 min was 4.2 +/- 0.7 pg fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0

Year Published

1991
1991
2008
2008

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 15 publications
0
10
0
Order By: Relevance
“…A vari ety of experimental approaches ranging from passive immuni zation against TRH [6,19] ablation of the PVN [20], hypophy sial portal blood collection for the direct measurement of TRH [8,9], determination of TRH in ME tissue [7] or characteriza tion of anterior pituitary TRH binding sites [21 ] have resulted in opposing views as to whether hypothalamic TRH release is regulated by thyroid hormone. Since direct measurement of TRH in vivo is complicated by the dilTicult technical nature of the approach (either hypophysial portal blood collection or push-pull perfusion experiments) and by the extremely short half-life time of TRH [22,23], we tested the effect of altered thyroid status on the in vitro release o f TRH and another proTRH derived peptide which is not recognized in the TRH RIA.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A vari ety of experimental approaches ranging from passive immuni zation against TRH [6,19] ablation of the PVN [20], hypophy sial portal blood collection for the direct measurement of TRH [8,9], determination of TRH in ME tissue [7] or characteriza tion of anterior pituitary TRH binding sites [21 ] have resulted in opposing views as to whether hypothalamic TRH release is regulated by thyroid hormone. Since direct measurement of TRH in vivo is complicated by the dilTicult technical nature of the approach (either hypophysial portal blood collection or push-pull perfusion experiments) and by the extremely short half-life time of TRH [22,23], we tested the effect of altered thyroid status on the in vitro release o f TRH and another proTRH derived peptide which is not recognized in the TRH RIA.…”
Section: Discussionmentioning
confidence: 99%
“…Szabo et al [6] concluded from their in vivo studies that the hypersecretion of TSH following thyroidectomy is largely independent of TRH control, while Mori and Yamada [7], on the other hand, reported changes in the median eminence (ME) con tent of TRH following thyroidectomy consistent with in creased TRH secretion. Further, studies involving the direct Received: April 2, 1990 Accepted after revision: October 24, 1990 measurement of TRH in hypophysial portal plasma have not clarified whether hypothalamic TRH secretion is regulated by thyroid hormone [8,9].Since it was possible that changes in thyroid status might affect the posttranslational processing of proTRH and thereby result in an altered pattern of synthesis and release of TRH vis-a-vis other proTRH-derived peptides, we studied the effects of hypothyroidism and hyperthyroidism on the hypothalamic content and release of preproTRH2s-so, the N-terminal se quence of proTRH, as well as TRH itself. …”
mentioning
confidence: 99%
“…Rats with signs of infection, continued weight loss or incorrect placement of the cannula [22] were excluded from the experiment (n = 21). Three weeks later, the mediobasal hypo thalamus was perfused as described before [22][23][24], Artificial cerebro spinal fluid was delivered at a rate of 20 ¡.tl/min and perfusate was col lected continuously for 120 min into tubes kept on melting ice. Transit time from the tip of the cannula to the sample tube was 5-7 min, and every 15 min a new sample was begun.…”
Section: Methodsmentioning
confidence: 99%
“…In the present study, push-pull per fusion of the mediobasal hypothalamus was used to determine the in vivo release of TRH and catecholamines in male rats ex posed to cold. Previous evidence has suggested that push-pull perfusion of the mediobasal hypothalamus is a valid method for the estimation of in vivo release of TRH, dopamine and adrena line [22][23][24]. …”
mentioning
confidence: 99%
“…This may be a mechanism by which T 4 can be adequately maintained at a developmental time when it is uniformly important. THs (T 4 and T 3 ) exert a negative feedback effect on the release of pituitary TSH and on the activity of hypothalamic TRH neurons 18, 19, 124 . Although it is clear that TH regulates the expression of TSH 153–155 and TRH 18, 123, 124, 156 in a negative feedback manner, it is also clear that the functional characteristics of negative feedback must include more than simply the regulation of the gene encoding the secreted protein/peptide.…”
Section: Thyroid Hormone Insufficiency—to What Extent Can Compensatormentioning
confidence: 99%